Professione insegnante Idee e modelli di formazione - Loredana, Perla; Martini, Berta (Didattica generale e disciplinare - Open Access, 2019)
Nowadays, what's the idea of ​​professionalism for the teacher? And how is it possible to promote the professional development of teachers in the changing school? This volume offers a significant cross-section with the contributions of those scholars who have dealt with the "professional development" object, by looking at it from various theoretical perspectives.